Analysis of the Art Education Status in Various Regions of Meizhou City Based on Participation in Painting Competitions - Xu, LinLin (Pacific International Journal, 2024)
Meizhou, known for its Hakka culture and a strong commitment to education, has historical and cultural significance, with a rich tradition of education. This study examines the current state of art education in different regions of Meizhou City, focusing on teacher resources and the participation and outcomes of the "Lin Fengmian Cup" painting competition in 2021. The study analyzes teacher resources and educational outcomes in both urban and rural areas, revealing disparities. Based on data collected from the painting competition, it is evident that participation and performance in art education vary significantly across regions. Urban areas tend to have higher participation and better outcomes, reflecting greater access to resources and opportunities. In contrast, economically underdeveloped rural areas face challenges in art education. The study underscores the importance of addressing these disparities, enhancing teacher resources, and providing policy and financial support for art education in less-developed regions. Promoting educational equity and advancing comprehensive quality education are essential for fostering well-rounded students and promoting social progress.